Competitive performance of the Mexican fruit production, 1980-2011 - Schwentesius Rindermann, Rita; Sangerman-Jarquín Dora Ma. (Revista Mexicana de Ciencias Agrícolas, 2018)
In order to analyse the competitiveness of the Mexican fruit production, a macroeconomic approach was used, considering variables as indicators of fruit production and its relationship to the agricultural economy and indicators of trade liberalization and international trade, which were interrelated between themselves. During 1980-2011, the production of fruits in Mexico grew at an average annual rate of 2.04%, while the value of production increased 0.15%, this phenomenon is explained by 80.04% due to the increase in the area, 11.4% due to innovations and, 8.16% for the interaction of both of them. The additive revealed comparative advantage and food self-sufficiency rate had a constant development; however, during the years 2008 and 2011, have been decreased. Even though, fruit production in Mexico is constantly increasing, its competitiveness in the national and international level has fallen, as it depends on several factors. The comparative advantages such as geographical location, climate, natural resources or labour, allowed complementarity actions with other markets and, increase in the competitiveness. However, nowadays, these are not decisive questions to ensure the permanence of fruit production in the markets. Finally, fruit production shows an extensive increased behaviour because yields grow in a lesser extent than the surface. In order to ensure its permanence in the international market is necessary that, the producers become increasingly competitive and, implement strategies to continue that work.